New National Art – New (?) Polish Mythology - Budzińska, Justyna (Sensus Historiae, 2023)
The article is an attempt to answer the question about the myth-creating potential of the so-called “new national art” (objects that appeared in the exhibition of the same title). Looking at selected, more and less artistic practices, I consider them in the context of “transtemporal nodes” and the “national sensorium,” placing them between two poles: God and Homeland. Despite the huge diversity of forms, fields and contexts from which they come (film, sculpture, press, music, sport, religion) and their specificity in relation to the official, gallery and museum circulation, they all have one basic task, which is to strengthen national identity, identify with “Polishness” and affective patriotism.